Analisis Program Makan Bergizi Gratis Terhadap Pemberdayaan Petani Lokal di Kabupaten Lebak - Abdul Rojak; Jaka Permana; Mahrus Helmi; Reihan DWI Prayudi (Suwaib Amiruddin Foundation, 2026)
Abstract This study aims to analyze the implementation of the Free Nutritional Meals (MBG) Program towards empowering local farmers in Lebak Regency. The MBG Program is a national policy that focuses not only on providing nutrition but also has the potential to encourage strengthening the local economy through the utilization of local agricultural products. This study uses a qualitative descriptive approach with the primary data source being an in-depth interview with one key informant from the Rangkas Bitung Barat Nutrition Fulfillment Service Unit (SPPG) and secondary data obtained from news reports and related documents. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results show that the implementation of the MBG Program has involved local farmers as food suppliers, particularly vegetables, thus opening market access and opportunities for increasing income. However, farmer empowerment is still partial because farmer involvement has not been integrated comprehensively and sustainably. This study contributes to fostering public policy studies, particularly regarding the role of the national nutrition program in supporting the economic empowerment of local farmers.. Penelitian ini bertujuan untuk menganalisis pelaksanaan Program Makan Bergizi Gratis (MBG) terhadap pemberdayaan petani lokal di Kabupaten Lebak. Program MBG merupakan kebijakan nasional yang tidak hanya berfokus pada pemenuhan gizi, tetapi juga berpotensi mendorong penguatan ekonomi lokal melalui pemanfaatan produk pertanian setempat. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan sumber data utama berupa wawancara mendalam dengan satu informan kunci dari Satuan Pelayanan Pemenuhan Gizi (SPPG) Rangkas Bitung Barat serta data sekunder yang diperoleh dari berita daring dan dokumen terkait. Analisis data dilakukan melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa pelaksanaan Program MBG telah melibatkan petani lokal sebagai pemasok bahan pangan, khususnya komoditas sayuran, sehingga membuka akses pasar dan peluang peningkatan pendapatan. Namun demikian, pemberdayaan petani masih bersifat parsial karena keterlibatan petani belum terintegrasi secara menyeluruh dan berkelanjutan. Penelitian ini memberikan kontribusi dalam memperkaya kajian kebijakan publik, khususnya mengenai peran program gizi nasional dalam mendukung pemberdayaan ekonomi petani lokal.